Analisis Faktor Risiko Obesitas dan Hipertensi dengan Kejadian Diabetes Melitus Tipe 2 di Rumah Sakit Umum Daerah Kota Kendari - Asmarani Asmarani; Andi Cahaya Tahir; Anisa Adryani (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2017)
ABSTRACTBackground:Type-2 Diabetes Mellitus is one type of diabetes that is the highest rates of incidence. Type-2 DM is a metabolic disorder with a characteristics of chronic hyperglycemia that occurs due to insulin resistance or lack of insulin secretion. Based on basic medical research showed that prevalence of type-2 DM in Indonesia keep on Increasing. Increasing cases of diabetes are theoretically cannot be separated from the risk factors that affect it. Purposes:This research aims to determine whether obesity and hypertension is a risk factor in the occurrence of type-2 DM. Methods:This research is observational analytic research with case-control matching design. The population were all patients who visited the RSUD Kota Kendari in September-December 2016. The sampling method is purposive sampling with the cases are those patient who was diagnosed with type-2 DM and the control are not. The samples are 136 people with the comparison cases and controls is 1:1 so that the number of cases-samples are 68 people and controls-samples are 68 people who had been matched such as age and gender. The instrument of this research are the weight-scales and microtoice to assess the nutritional status with calculation of BMI and also stethoscope and sphygmomanometer to measure the blood pressure. Data were analyzed by determining the odds ratio. Data was considered significant if UL and LL does not include the value of 1. Result:The results of this research showed that obesity and hypertension are a risk factor for the occurrence of type-2 DM with the results of statistical tests of obesity obtained OR : 7,164., CI 95% : 3,365-15,250 and hypertension obtained OR : 4,166., CI 95% : 2,026-8,567. Conclusion: The conclusions of this research is that obesity and hypertension are a risk factor in the incidence of type-2 DM in RSUD Kota Kendari in 2016.Keywords: Type-2 Diabetes Mellitus, Obesity, Hypertension